Abstract ID: 1 Elastic scattering in FLUKA code for MONDO experiment: characterization of the secondary fast and ultrafast neutrons emitted in particle therapy. (October 2017) - Giacometti, V.; Patera, V.; Mirabelli, R.; Pinci, D.; Sarti, A.; Sciubba, A.; Traini, G.; Battistoni, G.; Marafini, Michela
Abstract : The particle therapy (PT) is a modern technique of non-invasive radiotherapy mainly devoted to the treatment of tumours untreatable with surgery or conventional radiotherapy, because localised closely to organ at risk[1] . The risk of developing a radiogenic second malignant neoplasm, years or decades after undergoing a PT treatment is one of the main concerns in PT administration and planning. Since neutrons can release a significant dose far away from the tumour region, precise measurements of their flux, production energy and angular distributions is eagerly needed to improve the analytical models and the Monte Carlo simulation underlying the treatment planning systems, to predict the normal tissue toxicity in the target region and the risk of late complications in the whole body[2] . The MONDO (MOnitor for Neutron Dose in hadrOntherapy) project is devoted to the construction of a secondary fast and ultrafast neutron tracker and to characterise secondary neutron component in the range of [10–400] MeV[3] . The detector, based on the tracking of the recoil protons produced in two consecutive (n, p) elastic scattering interactions, is a matrix of thin scintillating fibres, arranged in layer x–y oriented (10 × 10 × 20 cm 3, with fibers of square cross sections 250 μm thick). The detector is under development, the construction is expected to be completed by the end of the year to start the experimental tests at proton and carbon ion therapy centres. A Monte Carlo FLUKA code has been developed to study the detection efficiency with double scattering events and to study the possible background due to inelastic scattering. One of the most important goal to be achieved in the simulation study is the estimation of the achievable energy resolution of the incoming neutrons. The details of the simulation and the results from the design study will be presented and discussed.